PWE-134 Outcomes For Liver Disease Patients Admitted to a District General Hospital. (4th June 2013) - Paranahewa, S; Allen, L; Toms, C; Lalloo, A; Kulhalli, V; Guinane, M; Rochford, A; Dias, A
Abstract : Introduction: In the UK, liver disease is the 5 th commonest cause of death. A recent BSG commissioning report states that there were 43, 694 hospital episodes due to liver disease with a mortality rate of 15.5% and median age of death of 59 1 . The guidelines recommend that all liver disease should be managed by a hepatologist. Newham University Hospital (NUH) serves a socially deprived and ethnically diverse population of 290, 000. Methods: All patients with a primary diagnosis of liver disease admitted to NUH from 1 April 2012 to 31 October 2012 were included in this study. Patients were identified from the on-call admission lists and electronic patient records and admission notes were checked for suitability. Patients admitted with alcohol withdrawal but without underlying liver disease were excluded. We examined the outcomes of all liver patients admitted during this time period. Results: 78 patients were admitted, of which 9 had ≥2 admissions. The demographic data and outcomes are listed in Table 1 . The ethnic variation reflected that of the local community. The main causes of liver disease were alcoholic liver disease (56%), viral hepatitis (22%) and drug-induced hepatitis (12%). The commonest reason for admission was decompensated liver disease seen in 32% of patients. 14.5% of patients experienced variceal haemorrhage at or during admission. There was a significant difference in mortality, in-hospital complications and the need for tertiary centre referral between patients with and without cirrhosis. The commonest in-hospital complications were infection and renal dysfunction; 16% of our patients required ICU support. There was no significant difference in median length of stay (LOS) between patients with and without cirrhosis. However patients with cirrhosis had more complex discharge requirements as demonstrated by referral to social services. Conclusion: Patients with cirrhosis have significantly more complex in hospital stay and discharge needs compared to patients without cirrhosis. Our study has shown a significantly lower mortality for patients with liver disease than previous studies. We suggest that management by a hepatologist and access to tertiary services improves mortality. The complexity of patients with cirrhosis suggests that a multi-professional team is required to reduce overall LOS. Disclosure of Interest: None Declared. Reference: http://www.bsg.org.uk/images/Commissioning_report/BSG_Commissioning%20Report.pdf